PERILAKU LENTUR BALOK CASTELLATED MODIFIKASI DENGAN PENYAMBUNG PROFIL SIKU DAN PERKUATAN TULANGAN KOMPOSIT MORTAR - AZWANDA, AZWANDA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Beam is a structure that has a bending moment whose strength is influenced by the moment of inertia of the beam. Therefore, to increase the moment of inertia without having to increase the size of the profile can be done by modifying the W-Shapes. Because most of the bending moment acting on W-Shapes has been endured by the wings, then the reduction in area of the body to a certain extent will not lower the flexural capacity of the W-Shapes. Modified form W-Shapes into castellated steel beams have different shapes hole openings variations, ranging from hexagonal, square, circle or combination of all three. Can also be modified to increase the flexural steel reinforcement and stiffness by using angles shapes and combined with using composite mortar. This study aims to conduct a study on the behavior of the flexural capacity then be compared with previous studies. The object of research is the junction modifications castellated beam connective with angles shapes diagonally after reinforced with bars D16 and mortar containing added ingredients such as Viscocrete-10. Beam used has a height of 300 mm, width 75 mm and length of span 3000 mm. The method of testing is done by using two point static loaded vertically with a review of the bending behavior. From the test results and theoretical calculations can be drawn several conclusions , among others : the bending capacity of castellated beams generated by modification with junction angles and reinforcement mortar composites based on a combination of test results is equal to 250.3 KN with an average increase of 38.76 % from previous studies. Deflection values due to the gradual imposition of castellated beams modified composite with a reinforcement decreased when compared with the composite castellated beams from previous studies with the maximum deflection value composite castellated beam modification of 30.07 mm. The resulting deflection values indicate that the modification of composite castellated beams with reinforcement having a higher level of service life than previous research . Efficient use of modified composite castellated beams with reinforcement compared with previous studies in terms of the moment capacity increased torque capacity by 2.1 % , in terms of heavy weight also decreased by 52 % and in terms of production budget price decreased by 32.46 % .